Strategi Manajemen Program Guru Tamu dalam Parenting untuk Mencegah Degradasi Moral Siswa SMK - Haryanto, Danni; Sauri, R. Supyan (Jayapangus Press, 2025)
Moral degradation among vocational high school (SMK) students has become an increasingly worrying issue, marked by an increase in deviant behavior, weak social ethics, and a decline in character values. Strategic prevention efforts are needed, one of which is through the active involvement of parents in character education through a parenting-based guest teacher program. This study aims to examine strategies for developing guest teacher programs in parenting as an effort to prevent moral degradation among SMK students. This study uses a qualitative approach with a case study method conducted at one of the SMKs in Indonesia. Data collection techniques were carried out through in-depth interviews, observations, and documentation of the principal, teachers, parents, and guest teacher sources. The results show that the development of guest teacher programs in parenting is carried out through four main strategies: first, participatory program planning involving school and community stakeholders; second, selection of competent resource persons who understand the principles of family education; third, implementation of programs that focus on current issues related to adolescent morality; and fourth, continuous evaluation to improve the effectiveness of program implementation. The support of the principal, the active involvement of parents, and cooperation with external institutions proved to be factors that strengthened the success of the program. This study concluded that the guest teacher program in parenting has strategic potential in building synergy between schools and families to strengthen student character and prevent moral degradation in a preventive and sustainable manner.